Analysis Of State Finances Within The Framework Of State Administrative Law - Maria MT Manurung; Syifa Fajastia (Program Pascasarjana UIN Sumatera Utara Medan, 2021)
This paper discusses state financial law from the perspective of state administrative law, which plays a crucial role in governance. State finance encompasses all state rights and obligations that can be valued in money, and its management must be orderly, transparent, and accountable. This research aims to understand the definition, scope, position, principles, oversight mechanisms, and responsibilities of administrative officials in managing state finances. The discussion results indicate that state financial law is a subset of public law that regulates the acquisition, management, and use of state funds based on principles of good governance, such as transparency, accountability, efficiency, effectiveness, and legal compliance. Oversight is carried out through internal and external mechanisms by authorized institutions, while accountability is manifested in auditable financial reports. Furthermore, state administrative officials have legal responsibilities that include administrative, civil, criminal, and moral liability. Therefore, state financial law is not merely technical but also a crucial instrument in realizing clean, effective, and accountable governance for the benefit of the public.